Using metaphors to get rid of a speech defect by Roman Jacobsen - Rashid, Huda Salah; Huseen, Hatem Kareem (Journal of Humanities & Social Sciences, 2020)
Praise be to Allah the Lord of the Worlds, prayer and peace be upon Ashraf senders and his family and his family companions either after: Vtad studies linguistics and one of the science of language that has developed a fast in a period of short, entered most of the fields of science and life different, and addressed various phenomena of language and non - language, has had to Ross’s role significantly in the development and continuation of this field of scientific their researches and symposia and institutions of different, and these scientists Roman Jakobson, who has the role of a great in the development and discovery of theories and issues of linguistic differences, as well as for diseases of language, and the issues of technical and other, and the issues that dealt with Roman Jakobson with regard to diseases of words is aphasia verbal and treatment employing metaphor to get rid of these defects articulatory, and based also on the development of scientific The medical office in America used it to serve and treat verbal aphasia, as well as its classification of verbal confinement. The stated research entitled (employment of metaphor in the disposal of the defect Alntqa when Roman Jakobson), was a plan research dealt with the definition of abbreviated Proman Jacobson, then the definition of imprisonment verbal and types, definition Borrowing and types when Roman Jakobson, followed by methods of treatment for by metaphor, and a the conclusion that summarizes the most important what reached the search of results